Maximum proportion of masks worn: Collaborative efforts in Japanese professional football - Tetsuo Yasutaka; Masaki Onishi; Wataru Naito; Yoshiaki Bando; Tomoaki Okuda; Michio Murakami (Elsevier, 2024)
Mass gathering events in Japan have gradually mitigated their novel coronavirus disease (COVID-19) control regulations, along with a minimum infection risk. The Japan Professional Football League (J.League) conducted pilot surveys on holding events with chant cheers. In this commentary, we introduce the collaborative efforts based on scientific knowledge among experts, J.League, and their fans. We performed risk assessment in advance, by updating a previously developed model. We further observed the average proportion of masks worn, chant cheering time of participants, and CO2 levels in the stand. The number of new COVID-19 cases in an event with 5,000 chant cheering participants and 35,000 non-chant cheering participants was estimated to be 1.02 times of an event, with 40,000 non-chant cheering participants. The average proportion of masks worn during the game was 98.9 %, for chant cheer participants. The chant cheering participants spent 50.0-51.1 % of their time chant cheering. Monitored average CO2 levels were ≤ 540 ppm, suggesting high ventilation rates in the stand. The high proportion of masks worn represents the willingness of norm-conscious fans to cooperate in regular recovery of the sport. This has proved to be one of the successful models for future mass gathering events.